Using a Game Development Platform to Improve Advanced Programming Skills - Poolsawas, Banyapon; Niranatlamphong, Winyu (Journal of Reviews on Global Economics, 2017)
A computer game is one of the most efficient instructional media for improving learners' programming skills. Implementing a game development platform or a game engine as an instruction tool provides benefits to learners. This paper observes progress in the learning process, and measures how long learners take to find solutions. The participants in the experiment were divided into two groups. The first group used traditional instructional media, such as lecturing, studying class materials, and solving assigned programming assignments. On the other hand, the second group attended the lectures, similar to the first group, and used a game development platform as instructional media to solve assigned programming assignments. The results showed that the progressive skills of the Game Development Platform learners were higher, and the problem-solving time they spent was lower.